A Critical Review of Biofuels as an Alternative Fuel to Diesel in Gulf Regional Corporation (GCC) Region: Current Market Trends and Future Opportunitie - Faisal O. Mahroogi; Sunny Narayan; Muhammad Usman Kaisan; Abdulkabir Aliyu; Ibrahim Yahuza; Ivan Grujić; Nadica Stojanović (Communications - Scientific letters of the University of Zilina, 2022)
Bio Fuels are considered as good alternatives for conventional fossil fuels. By the year 2020, in the GCC region these fuels are able to meet around 0.5 - 1% of total transportation fuel demand. This industry grew at rate of 3.4% over the period of 2015-2020 with a strong projected growth in the Kingdom of Saudi Arabia (KSA). Bio fuels are used to operate automotive for mining and construction industries. Critical barriers in foreign investments pose a major challenge for growth of this sector in the GCC region. The presented work discusses situation and growth predictions of Bio-Fuel industry in the GCC region. It also discusses about current growth, trends, opportunities and challenges being faced by major companies operating in the GCC region.